Pengaruh Beban Kerja, Kepuasan Kerja, dan Keadilan Organisasi terhadap Kinerja: Survei pada Karyawan Outsourcing di PT So Good Food Boyolali - Enjelia Enjelia; Unna Ria Safitri; Alean Kistiani Hegy Suryana; Hari Purwanto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This research investigates the influence of workload, job satisfaction, organizational justice contribute to determining the performance levels of outsourced workers at PT So Good Food Boyolali. The practice of employing contract labor in the food processing sector creates complex dynamics—from both psychological and managerial perspectives—making the identification of productivity drivers an urgent managerial necessity. This research employs an associative quantitative survey design, utilizing structured questionnaires distributed to 117 outsourced employees in the Ready-to-Eat (RTE) division, selected via purposive sampling. The data were analyzed using multiple linear regression in SPSS version 32, applying a natural logarithm transformation to meet normality distribution requirements. Partial test results indicate that workload did not have a statistically significant effect on employee performance (t = -1.204; significant = 0.231). Conversely, job satisfaction (t = 5.088; sig = 0.000) and organizational justice (t = 4.601; sig = 0.000) were found to have significant effects. A simultaneous test of the three variables revealed that they explain 69.8% of the variation in employee performance (F = 86.956; sig = 0.000). These findings imply that strategies to enhance the productivity of outsourced workers should focus on strengthening job satisfaction and improving perceptions of justice, regardless of the intensity of standardized operational workloads.